2020
DOI: 10.1177/0284185120980144
|View full text |Cite
|
Sign up to set email alerts
|

Detecting lymph node metastasis of esophageal cancer on dual-energy computed tomography

Abstract: Background Using conventional computed tomography (CT), the accurate diagnosis of lymph node (LN) metastasis of esophageal cancer is difficult. Purpose To examine dual-energy CT parameters to predict LN metastasis preoperatively in patients with esophageal cancer. Material and Methods Twenty-six consecutive patients who underwent dual-energy CT before an esophageal cancer surgery (19 patients with LN metastases) were analyzed. The included LNs had a short-axis diameter of ≥4 mm and were confirmed to be resecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…The distribution of iodine in the tissue is strongly correlated with local blood volume and vascular density [16]. Several studies have shown that IC correlates well with higher blood ow and vascularization [14,[17][18][19][20][21][22]. In our study, IC in the AP and VP was signi cantly different among the three groups, as tumor grade increased, it also increased.…”
Section: Discussionsupporting
confidence: 43%
“…The distribution of iodine in the tissue is strongly correlated with local blood volume and vascular density [16]. Several studies have shown that IC correlates well with higher blood ow and vascularization [14,[17][18][19][20][21][22]. In our study, IC in the AP and VP was signi cantly different among the three groups, as tumor grade increased, it also increased.…”
Section: Discussionsupporting
confidence: 43%
“…The mean age of patients in the 16 included studies varied from 34.0±7.8 to 59.5±8.7 years, while the percentage of males ranged from around 0.0% to 70.9%. Moreover, 7 of the 16 studies included patients with thyroid cancer ( 16 , 23 , 24 , 29 , 30 , 33 , 36 ), 4 studies included patients with colorectal cancer ( 25 , 28 , 35 , 37 ), and the remaining 5 studies included patients with esophageal cancer, liver cancer, breast cancer, squamous cell carcinoma of the oropharynx, or lung cancer ( 26 , 27 , 31 , 32 , 34 ). Table 1 details the patient characteristics of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…After a reading of the titles and abstracts of these 257 original studies, 202 papers were excluded. Then, full texts were read in detail, and a rescreening was performed based on the inclusion and exclusion criteria, resulting in a final sample of 16 eligible studies for inclusion in this meta-analysis (16,(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37). The flowchart outlining the screening process is shown in Figure 1.…”
Section: Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al, 12 in their findings for predicting LNM in gastric cancer noted that the IC of cancer foci was closely associated with LNM. Su et al 13 indicated significant differences in NIC in esophageal cancer foci in patients with metastatic and non-metastatic lymph. This study included 3 DECT parameters of IC, NIC, and λ HU of intravenous phase PTC, and all 3 parameters were correlated with CLNM of PTC by univariate statistical analysis ( P < .05), and the results of the multivariate analysis showed that only intravenous phase NIC was an independent predictor of CLNM, and when NIC ≥.68, patients with PTC had an increased risk of developing CLNM.…”
Section: Discussionmentioning
confidence: 99%